Degradation of propanil by Acinetobacter baumannii DT immobilized in alginate - Danh Duc Ha; Thi Oanh Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
The herbicide propanil has been widely applied in Vietnam and around the world to control weeds. In this study, Acinetobacter baumannii DT isolated from soil was used to determine propanil degradation. Degradation experiments were carried out with condensed cells at 109 CFU/ml with both free and immobilized forms of the bacteria. Propanil degradation rates by bacteria immobilized in alginate were higher than those of free cells at the same concentrations. The degradation curve as a function of concentration fit well to the degradation kinetics described by the Edwards model with a maximum degradation of 0.034±0.003 mM/h for free cells and 0.053±0.005 mM/h for immobilized cells. Moreover, the immobilized bacteria could tolerate higher propanil concentrations and degrade propanil in a well-known herbicide more effectively compared to the freely suspended bacteria. These results demonstrate that A. baumannii DT immobilized in alginate is suitable for degradation of propanil in herbicides.